Wilson loop Langevin equations for U (1) lattice gauge theory. - Aldazabal, Gerardo Marcelo; Dagotto, E.; González Arroyo, A.; Parga, Nestor Omar (American Chemical Society, 1983)
Fil: Aldazabal, G. Comisión Nacional de Energía Atómica; Argentina